LO72: Implementation of an educational program to improve the cardiac arrest diagnostic accuracy of ambulance communication officers: a concurrent control before-after study. (15th May 2017) - Vaillancourt, C.; Kasaboski, A.; Charette, M.; Calder, L.; Boyle, L.; Nakao, S.; Crete, D.; Kline, M.; Souchuk, R.; Kristensen, N.; Wells, G.A.; Stiell, I.G.
Abstract : Introduction: Most ambulance communication officers receive minimal education on agonal breathing, often leading to unrecognized out-of-hospital cardiac arrest (OHCA). We sought to evaluate the impact of an educational program on cardiac arrest recognition, and on bystander CPR and survival rates.Methods: Ambulance communication officers in Ottawa, Canada received additional training on agonal breathing, while the control site (Windsor, Canada) did not. Sites were compared to their pre-study performance (before-after design), and to each other (concurrent control). Trained investigators used a piloted-standardized data collection tool when reviewing the recordings for all potential OHCA cases submitted. OHCA was confirmed using our local OHCA registry, and we requested 9-1-1 recordings for OHCA cases not initially suspected. Two independent investigators reviewed medical records for non-OHCA cases receiving telephone-assisted CPR in Ottawa. We present descriptive and chi-square statistics.Results: There were 988 confirmed and suspected OHCA in the "before" (540 Ottawa; 448 Windsor), and 1, 076 in the "after" group (689 Ottawa; 387 Windsor). Characteristics of "after" group OHCA patients were: mean age (68.1 Ottawa, 68.2 Windsor); Male (68.5% Ottawa, 64.8% Windsor); witnessed (45.0% Ottawa, 41.9% Windsor); and initial rhythm VF/VT (Ottawa 28.9, Windsor 22.5%). Before-after comparisons were: for cardiac arrest recognition (from 65.4% to 71.9% in Ottawa p=0.03; from 70.9% to 74.1% in Windsor p=0.37); for bystander CPR rates (from 23.0% to 35.9% in Ottawa p=0.0001; from 28.2% to 39.4% in Windsor p=0.001); and for survival to hospital discharge (from 4.1% to 12.5% in Ottawa p=0.001; from 3.9% to 6.9% in Windsor p=0.03). "After" group comparisons between Ottawa and Windsor (control) were not statistically different, except survival (p=0.02). Agonal breathing was common (25.6% Ottawa, 22.4% Windsor) and present in 18.5% of missed cases (15.8% Ottawa, 22.2% Windsor p=0.27). In Ottawa, 31 patients not in OHCA received chest compressions resulting from telephone-assisted CPR instructions. None suffered injury or adverse effects.Conclusion: While all OHCA outcomes improved over time, the educational intervention significantly improved OHCA recognition in Ottawa, and appeared to mitigate the impact of agonal breathing.